La balanza de pagos y su incidencia en el crecimiento económico del Ecuador en el periodo 2000-2013. Aplicación del modelo de Thirlwall - Coello Alvear, Carlos Ricardo (2016)
A payment balance and its influence on Ecuadorian economy growth during 2000-2013 is a research which includes Thirlwall model implementation. This research analyses, if there is any growth constraint from external sector; specifically about net exportations of services and goods. Also, there is an analysis, if there is any cointegration relationship between Gross Domestic Product and goods and services exportations. This research displays some book references and quantitative information through charts, graphic and figures. It includes some result analysis and discussion. This research develops the following structure: A Referential Framework is displayed on first chapter which contains research guidelines. On the second chapter, there is a Theoretical Framework which presents information about economy theory. It keeps a close relationship among economy growth, payment balance and a relationship between economic growth and trade imbalance. This research has a literature review about concepts, definitions, components, characteristics and theories to support it. A methodological framework is developed on the third chapter. It contains information about its research methodology which includes an analysis about growth behavior and the Ecuadorian payment balance. Also, the gotten outcomes are based on cointegration relationship between Gross Domestic Product and goods and services exportations. Conclusions and recommendations are presented on fourth chapter. Conclusions are the final result after finishing this research; the suggestions are given as guidelines to a future research.